Design and synthesis of water soluble β-aminosulfone analogues of SCH 900229 as γ-secretase inhibitors. Issue 23 (1st December 2016) - Wu, Wen-Lian; Burnett, Duane A.; Clader, John; Greenlee, William J.; Jiang, Qin; Hyde, Lynn A.; Del Vecchio, Robert A.; Cohen-Williams, Mary E.; Song, Lixin; Lee, Julie; Terracina, Giuseppe; Zhang, Qi; et al.
Graphical abstract: Abstract: In this paper we describe our strategy to improve the aqueous solubility of SCH 900229, a potent PS1-selective γ-secretase inhibitor for the treatment of Alzheimer's disease. Incorporation of ionizable amino groups into the side chain terminal generates water soluble β-aminosulfone analogues of SCH 900229 that maintain robust in vitro potency and in vivo efficacy.